Transient modelling and simulation of a switched reluctance machine in different operating modes - Ali Asghar Memon; Chen Hao; Mazhar Hussain Baloch (Mehran University Research Journal of Engineering and Technology, 2023)
An appropriate numerical computational method and simplest model captures the performance of Switched Reluctance Machines (SRMs). Several papers and computer software-based simulation models are reported in the literature. Each model has its own merits and demerits. This paper proposes a mathematical model, based on a combination of voltage and mechanical equations, suitable for the transient running of a switched reluctance machine. The simulation results of current, torque and speed profile of SRM are produced under current chopping control and voltage pulse width modulation control. The proposed work has used experimental data of flux linkage and static torque in the mathematical model for best performance and control of the machine. The obtained simulation results are verified with experimental results. This model can be extended to a range of rotor position where the machine can be switched at decreased and increased inductance region which gives motoring and generating operation mode.